The carbon budget of a tundra in the north-eastern Russian Arctic during the snow free season and its stability in the 2003-2016 period - Dolman, H.; van Huissteden, J.; Dean, J.; Maximov, T.; Petrov, R.; Belelli Marchesini, L. (2020)
Large quantities of carbon are stored in the terrestrial permafrost of the Arctic region where the rate of climate warming is two to three times more than the global mean and the largest temperature anomalies observed in autumn and winter. The quantification of the impact of climate warming on the degradation of permafrost and the associated potential release to the atmosphere of carbon stocked in the soil in the form of greenhouse gases, thus further increasing the radiative forcing of the atmosphere, is a research priority in the field of biogeosciences. Land-atmosphere turbulent fluxes of CO2 and CH4 have been monitored at the tundra site of Kytalyk in north-eastern Siberia (70,82 N; 147.48 E) by means of eddy covariance since 2003 and 2008, respectively; regular measurement campaigns have been carried out since then. Here we present results of the seasonal CO2 budget of the tundra ecosystem for the 2003-2016 period based on observations encompassing the permafrost thawing season and analyze the inter-annual differences in the seasonal patterns of CO2 fluxes considering the separate the contribution of climatic drivers and ecosystem functional parameters relative to the processes of respiration and photosynthesis. The variability of the CO2 budget is also discussed in view of the impact of the timing and length of the snow free period. The Kytalyk tundra acted as an atmospheric carbon dioxide sink with relatively small inter-annual variability (-96.1±11.9 gC m-2) during the snow free season and the seasonal CO2 budget did not show any trend over time. The pronounced meteorological variability characterizing Arctic summers was a key factor in shaping the length of the carbon uptake period, which did not progressively increased despite its tendency to start earlier, and in determining the magnitude of CO2 fluxes. No clear evidence of inter-annual changes in the eco-physiological response parameters of CO2 fluxes to climatic drivers (global radiation and air temperature) was found along the course of the ...